Mineral trioxide aggregate pulpotomy: An ideal treatment option for management of talon cusp - Vijay Kumar; Amrita Chawla; Ajay Logani; Naseem Shah (Wolters Kluwer Medknow Publications, 2012)
To use mineral trioxide aggregate (MTA) in prophylactic management of talon cusp. Talon cusp is an endodontic oddity that possesses a treatment challenge to the clinician, especially when it causes esthetic and functional problems. Management ranges from periodic gradual reduction to radical removal followed by vital pulp/endodontic therapy. MTA has replaced calcium hydroxide as pulp capping material because of its superior properties. A 12-year-old boy reported with a complaint of irregular teeth. Clinical and radiographic examination revealed talon cusp on maxillary left central incisor. Radical removal of talon cusp and MTA pulpotomy was performed. The 4-year follow-up showed the positive pulp vitality test without any radiographic changes, emphasizing the use of MTA pulpotomy in successful management of talon cusp.